Concordance of in‐home 'smart' scale measurement with body weight measured in‐person. (26th May 2016) - Ross, K. M.; Wing, R. R.
Summary: Objective: Newer 'smart' scales that transmit participants' body weights directly to data collection centres offer the opportunity to simplify weight assessment in weight management research; however, little data exist on the concordance of these data compared with weights measured at in‐person assessments. Methods: We compared the weights of 58 participants (mean ± SD, body mass index = 31.6 ± 4.8, age = 52.1 ± 9.7 years, 86.2% Caucasian, 65.5% female) measured by study staff at an in‐person assessment visit to weights measured on the same day at home using BodyTrace 'smart' scales. These measures occurred after 3 months of an internet‐based weight management intervention. Results: Weight (mean ± SD) measured at the 3‐month in‐person assessment visit was 81.5 ± 14.7 kg compared with 80.4 ± 14.5 kg measured on the same day using in‐home body‐weight scales; mean bias = 1.1 ± 0.8 kg, 95% limits of agreement = −0.5–2.6. Two outliers in the data suggest that there may be greater variability between measurements for participants weighing above 110 kg. Conclusion: Results suggest good concordance between the measurements and support the use of the BodyTrace smart scale in weight management research. Future trials using BodyTrace scales for outcome assessment should clearly define protocols for measurement and associated instructions to participants (e.g. instruct individuals to weigh at the same time of day, similarly clothed). Finally, measure concordance should be investigated in a group of individuals weighing more than 110 kg.